Invasive cordgrass (Spartina spp.) in south‐eastern Australia induces island formation, salt marsh development, and carbon storage. (8th December 2017) - Kennedy, David M.; Konlechner, Teresa; Zavadil, Elisa; Mariani, Michela; Wong, Vanessa; Ierodiaconou, Daniel; Macreadie, Peter
Abstract: Invasive vegetation species can lead to major changes in the geomorphology of coastal systems. Within temperate estuaries in the southern hemisphere, especially Australia and New Zealand, the cordgrass Spartina spp. has become established. These species are highly invasive, and their prolific growth leads to the development of supratidal environments in formerly intertidal and subtidal environments. Here, we quantified the impact of Spartina invasion on the geomorphology and sequestration capacity of carbon in the sediments of Anderson Inlet, Victoria, Australia. Spartina was first introduced to the area in the 1930s to aid in land reclamation and control coastal erosion associated with coastal development. We found that Spartina now dominates the intertidal areas of the Inlet and promotes accretion (18 mm/year) causing the formation of over 108 ha of supratidal islands over the past 100 years. These newly formed islands are calculated to potentially contain over 5.5 million tonnes of CO2 equivalent carbon. Future management of the inlet and other Spartina ‐dominated environments within Australian presents a dilemma for resource managers; on the one hand, Spartina is highly invasive and can outcompete native tidal marshes, thereby warranting its eradication, but on the other hand it is likely more resilient to rising sea levels and has the potential for carbon sequestration. Whether or not the potential advantages outweigh the significant habitat change that is anticipated, any management strategies will likely require additional research into costs and benefits of all ecosystem services provided by Spartina including in relation to nutrient cycling, shoreline stabilisation, and biodiversity as well as in response to the longevity of carbon found within the sediments.